Measuring Collaborative Problem Solving Using Mathematics-Based Tasks - Susan-Marie E. Harding; Patrick E. Griffin; Nafisa Awwal; BM M. Alom; Claire Scoular (SAGE Publishing, 2017)
This study describes an online method of measuring individual students' collaborative problem-solving abilities using four interactive mathematics-based tasks, with students working in pairs. Process stream data were captured from 3,000 students who completed the tasks in the United States, Australia, Canada, Costa Rica, Singapore, and Finland. The data were transformed into indicators of collaborative problem-solving ability and were analyzed using item response modeling. The assessments employed in this study can be used as a teaching tool for introduction to algebraic concepts and as a measurement instrument for collaborative problem-solving ability. The paper describes the construction, calibration, and reliability of the tasks and considers validation issues, such as fairness between assessments for both partners and avoidance of cultural biases. Investigations into the dependencies between student scores provide evidence for convergent and discriminant validity.